2018
DOI: 10.1136/bjophthalmol-2018-312015
|View full text |Cite
|
Sign up to set email alerts
|

Possible connection of short posterior ciliary arteries to choroidal neovascularisations in eyes with pathologic myopia

Abstract: Swept-source OCT showed that some of the myopic CNVs were continuous with scleral vessels mainly the SPCA. Further studies to confirm angiographical continuity between these two components are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 28 publications
2
46
0
2
Order By: Relevance
“…Recently, in eyes with myopic CNV, SS-OCT showed that the connection between the CNV and the scleral vessels mainly originated from the short posterior ciliary arteries. 20 Kuehlewein et al reported that OCTA showed a large main feeder vessel in 75% of eyes with type 1 CNV. 21 In the current study, we found the feeder vessel in one of the five eyes, and the CNV signal was observed presumably originating from that vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in eyes with myopic CNV, SS-OCT showed that the connection between the CNV and the scleral vessels mainly originated from the short posterior ciliary arteries. 20 Kuehlewein et al reported that OCTA showed a large main feeder vessel in 75% of eyes with type 1 CNV. 21 In the current study, we found the feeder vessel in one of the five eyes, and the CNV signal was observed presumably originating from that vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using the OCTA have suggested that rupture of the Bruch's membranes may be the cause of macular atrophy developing after mCNV [88]. However, the combination of OCTA and SS-OCT in multimodal imaging has given promising results-suggesting that mCNV is directly supplied by the short posterior ciliary artery instead of the choroidal vasculature as previously postulated [89].…”
Section: Challenges In Imaging the Retinamentioning
confidence: 89%
“…Louzada et al [36] and Giuffre et al [37] reported that blood vessels originating from the sclera were found at the site of myopic CNVs. Recently Ishida et al [38] reported that the blood vessels of myopic CNVs were continuous to scleral branches of short posterior ciliary arteries (Fig. 9.11).…”
Section: Myopic Cnv and Cnv-related Macular Atrophymentioning
confidence: 98%
“…10 (continued) 11 Continuity between scleral perforating vessels and myopic choroidal neovascularization (CNV) in the atrophic phase[38]. (a) Fundus photograph of the right eye shows a sharpmargined macular atrophy around a CNV (arrow).…”
mentioning
confidence: 99%